Assessing the economic contribution of sports tourism events: A regional social accounting matrix analysis approach. Issue 3 (May 2022) - Pedauga, Luis E; Pardo-Fanjul, Ana; Redondo, Juan C; Izquierdo, José M
In the context of tourism, sports are one of the major attractions countries offer. There cannot be the slightest doubt about the relevance of sports activities for the economy. Previous studies assessing the economic impact of sporting events have usually been partial equilibrium studies. This article contributes to the emerging body of literature by explicitly incorporating four categories of sports tourism events (competitions, championships, tournaments, and leagues), so as to study the effects of sports tourism demand on the economic system in terms of income and added value. It further examines their relative, rather than individual, impact on the regional economy of Castile and Leon through a fixed price multiplier model based on the regional social accounting matrix. The results reveal that sports tourism events represent 3.1% of the regional gross domestic product, highlighting the importance of this sector for its economy.